Lebnicz formula for the product
"(f(x)g(x)) ^{(n)}= \\sum\\limits _{r=0}^{n}C^r_n(f )^{(n-r)}(x) (g )^{(r)}(x)"
"f(x)= 2x^{3}+x^{2}+x+2, g(x)=e^{2x}"
"(f(x)g(x)) ^{(4)}=((2x^{3}+x^{2}+x+2)e^{2x}) ^{(4)} = \\\\ \n = \\sum \\limits _{r=0}^{4} C^r_4(2x^{3}+x^{2}+x+2) ^{(4-r)} (e^{2x} )^{(r)}" =
"=\\sum\\limits _{r=0}^{n}C^r_4((2x^{3}+x^{2}+x+2) )^{(4-r)}(x) (e^{2x} )^{(r)}=\\\\=C^0_4((2x^{3}+x^{2}+x+2) )^{(4)}(x) (e^{2x} )+\\\\\n+C^1_4((2x^{3}+x^{2}+x+2) )^{(3)}(x) (e^{2x} )^{(1)}+\\\\+C^2_4((2x^{3}+x^{2}+x+2) )^{(2)}(x) (e^{2x} )^{(2)}+\\\\+C^3_4((2x^{3}+x^{2}+x+2) )^{(1)}(x) (e^{2x} )^{(3)}+\\\\+C^4_4((2x^{3}+x^{2}+x+2) )(x) (e^{2x} )^{(4)}"
"\\frac{}{}" "C^r_n=\\frac{n!}{(n-k)! k!} \n\u200b"
"C^0_4=\\frac{4!}{(4)! 0!}=1 \\\\ C^1_4=\\frac{4!}{(3)! 1!}=4\\\\ C^2_4=\\frac{4!}{(2)! 2!}=6\\\\C^3_4=\\frac{4!}{(1)! 3!}=4\\\\C^4_4=\\frac{4!}{(0)! 4!}=1"
"(2x^{3}+x^{2}+x+2) ^{(1)}=6x^{2}+2x^+1\\\\\n(2x^{3}+x^{2}+x+2) ^{(2)}=(6x^{2}+2x+1)^{(1)}=12x+2\\\\\n(2x^{3}+x^{2}+x+2) ^{(3)}=(12x+2)^{(1)}=12\\\\\n(2x^{3}+x^{2}+x+2) ^{(4)}=0"
"(e^{2x} )^{(1)}=2e^{2x} \\\\\n(e^{2x} )^{(2)}=4e^{2x}\\\\\n(e^{2x} )^{(3)}=8e^{2x}\\\\\n(e^{2x} )^{(4)}=16e^{2x}"
So
"((2x^{3}+x^{2}+x+2)e^{2x}) ^{(4)}=\\\\=1*0*e^{2x}+4*2*12 e^{2x}+ \\\\+6*4*(12x+2) e^{2x}+ \\\\+4*8*(6x^{2}+2x+1) e^{2x}+\\\\+1*16 (2x^{3}+x^{2}+x+2) e^{2x}=\\\\=e^{2x}(32x^3+208x^2+368x+208)"
Answer:
"\\frac{d^4}{dx^4} ((2x^{3}+x^{2}+x+2)e^{2x})=e^{2x}(32x^3+208x^2+368x+208)."
Comments
Leave a comment